2022
DOI: 10.15252/embr.202255782
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic chromosomal interactions and control of heterochromatin positioning by Ki‐67

Abstract: Ki-67 is a chromatin-associated protein with a dynamic distribution pattern throughout the cell cycle and is thought to be involved in chromatin organization. The lack of genomic interaction maps has hampered a detailed understanding of its roles, particularly during interphase. By pA-DamID mapping in human cell lines, we find that Ki-67 associates with large genomic domains that overlap mostly with late-replicating regions. Early in interphase, when Ki-67 is present in pre-nucleolar bodies, it interacts with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 86 publications
3
9
0
Order By: Relevance
“…It remains to be determined whether it interacts with components of heterochromatin, including HP1α, and whether its depletion affects the abundance of these proteins within heterochromatin and, consequently, its nanoscale organisation. However, our data are consistent with a recent genome‐wide mapping study which found that Ki‐67 binds centromere‐proximal regions marked with H3K9me3 in interphase (preprint: van Schaik et al , 2021). Also, the ability of Ki‐67 to adapt to different chromatin environments remains to be explored.…”
Section: Discussionsupporting
confidence: 92%
“…It remains to be determined whether it interacts with components of heterochromatin, including HP1α, and whether its depletion affects the abundance of these proteins within heterochromatin and, consequently, its nanoscale organisation. However, our data are consistent with a recent genome‐wide mapping study which found that Ki‐67 binds centromere‐proximal regions marked with H3K9me3 in interphase (preprint: van Schaik et al , 2021). Also, the ability of Ki‐67 to adapt to different chromatin environments remains to be explored.…”
Section: Discussionsupporting
confidence: 92%
“…This is the first time that Ki-67 has been linked directly to the control of replication. Interestingly, and taking advantage of the endogenously tagged cell line, we could follow Ki-67 localisation during replication, and we could see changes in its localisation pattern as DNA replication progresses with Ki-67 co-localising with the replication foci, particularly evident for the late replicating regions of the genome: this aligns partially with a recent report showing that Ki-67 interacts with of Lamin B1-depleted late replicating genomic regions [28].…”
Section: Discussionsupporting
confidence: 85%
“…Another phenotype linked to Ki-67 depletion is a compromised heterochromatin maintenance as revealed by the Ki-67 KO mouse model [13] or the RNAi study in hTERT-RPE1 cells [27] and positioning [28].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, GNL3 may play a larger role in the organization of centromeres, or other regions of heterochromatin, by keeping them in proximity to the nucleolus thanks to its long residency time (Meng et al , 2006). For example, GNL3 may mediate interactions between nucleolus and heterochromatin as proposed for Ki‐67 (Sobecki et al , 2016; van Schaik et al , 2022) and NPM1 (Holmberg Olausson et al , 2014), two proteins localized to the nucleolar rim like GNL3 (Stenstrom et al , 2020). It has been recently shown that genome organization is a determinant of the locations of replication origins (Emerson et al , 2022), therefore GNL3 may have a broader role in the regulation of replication origin firing.…”
Section: Discussionmentioning
confidence: 99%